Four new gelechioid species to honor Costa Rica's conservation of wild biodiversity (Lepidoptera) - Metz, Mark A.; Hallwachs, Winnie; Janzen, Daniel H. (Zootaxa, 2020)
We described four new gelechioid species from Costa Rica: Philtronoma cbdora Metz, new species; Tinaegeria carlosalvaradoi Metz, new species; Tinaegeria romanmacayai Metz, new species (Depressariidae: Tinaegeriinae revised status); and Percnarcha claudiadoblesae Metz, new species (Gelechiidae: Gelechiinae). We provide these honorifics to recognize commitment and devotion to conservation of biodiversity. The new species are all highly diagnostic among other species of Gelechioidea, and species of Tinaegeria and Percnarcha demonstrate striking mimesis for presumed wasp and beetle models. The family-group name Tinaegeriidae Hampson, 1893 is clarified, including the previously overlooked priority of the family-group name synonyms, and is placed as a valid subfamily in Depressariidae comprised of the genera Filinota Busck, 1911, Nematochares Meyrick, 1931, Philtronoma Meyrick, 1914, Profilinota Clarke, 1973, and Tinaegeria Walker, 1856.